2012
DOI: 10.1002/ana.23543
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells restore cortical rewiring after neonatal ischemia in mice

Abstract: This is the first study to describe MSC treatment after neonatal HI markedly reducing contralesional axonal remodeling induced by HI brain injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
48
0
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 44 publications
5
48
0
2
Order By: Relevance
“…We have shown before that HI can induce a decline in lateral arborization of MBP-positive fibers in the ipsilateral cingulum, defined as an increase in fiber coherency demonstrated by a more linear MBP pattern [23]. Figure 3d and e show that HI did not result in a significant increase in MBP-positive fiber coherency (indicating no significant reduction in lateral arborization of MBP-positive fibers) within the cingulum at D10 postinsult compared to sham-operated littermates.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…We have shown before that HI can induce a decline in lateral arborization of MBP-positive fibers in the ipsilateral cingulum, defined as an increase in fiber coherency demonstrated by a more linear MBP pattern [23]. Figure 3d and e show that HI did not result in a significant increase in MBP-positive fiber coherency (indicating no significant reduction in lateral arborization of MBP-positive fibers) within the cingulum at D10 postinsult compared to sham-operated littermates.…”
Section: Resultsmentioning
confidence: 84%
“…It is known that HI can induce changes in corpus callosum volume, which is associated with lateralizing motor deficits [22,23]. Therefore, we measured the thickness of the corpus callosum after HI and LPS+HI at the striatal level, both at the midline and in the contra- and ipsilateral hemisphere at D10 postinsult.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, stroke induces changes in the miRNA profile of MSCs and within their released exosomes [118]. In line with the broad neuroprotective effect exerted by MSCs, Van Velthoven et al demonstrated that local administration of MSCs could restore functional cortical rewiring and increase axonal connectivity in the ipsilesional hemisphere [119]. Remarkably, also intranasally administered MSCs can decrease brain damage upon neonatal stroke [120].…”
Section: Ischemic Strokementioning
confidence: 99%
“…IC is the most important type of white matter in the brain. 33 Motor axons form a tract running from the ipsilateral cortex and passing through the ipsilateral IC toward the contralateral spinal cord. FA is directly related to histological markers of myelination.…”
Section: Discussionmentioning
confidence: 99%